Fun with Matrix

Algebra Level 4

Let A = [ 2 3 0 1 ] A = \begin{bmatrix}{2} & {3} \\ {0} & {1}\end{bmatrix} . If A 20 2 A 19 + A = [ 2 b 0 0 ] A^{20} - 2A^{19} + A = \begin{bmatrix}{2} & {b} \\ {0} & {0}\end{bmatrix} , find the value of b b .


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Saail Narvekar
May 18, 2016

Nice problem and solution.. @Saail Narvekar ....... I did a bit different .. I found A , A 2 , A 3 A,A^2,A^3 and then it was easy to sense a pattern:-

A n = ( 2 n 3 ( 2 n 1 ) 0 1 ) \large A^n=\begin{pmatrix}2^n&3(2^n-1)\\0&1\end{pmatrix}

And then the answer follows..

Rishabh Jain - 5 years ago

Nice problem and solution. @Saail Narvekar

You can further improve your problem and solution by adding latex and text instead of just an image. You can find the latex guide here . Thanks!

Sandeep Bhardwaj - 5 years ago

Log in to reply

Thanks for the suggestion @Sandeep Bhardwaj .As this was the 1 st time posting questions in brilliant i had no idea about latex guide.

Saail Narvekar - 5 years ago

Log in to reply

Ping me anytime if you need any kind of assistance. :-)

Sandeep Bhardwaj - 5 years ago

Log in to reply

@Sandeep Bhardwaj hey @Sandeep Bhardwaj the latex code we write in publish box is the original form not visible after preview ??

Saail Narvekar - 5 years ago
展豪 張
May 29, 2016

Let I = [ 1 0 0 1 ] , B = [ 1 3 0 0 ] I=\begin{bmatrix}1&0\\0&1\end{bmatrix},B=\begin{bmatrix}1&3\\0&0\end{bmatrix}
These little properties allow us to find A n A^n easily: A = I + B A=I+B , I B = B I = B IB=BI=B and B n = B B^n=B for positive integers n n .
A n \;\;\;\;A^n
= ( I + B ) n =(I+B)^n
= i = 0 n C i n I i B n i =\displaystyle\sum_{i=0}^n C_i^n I^i B^{n-i} (usually this is not true, but this time it is, becuase I B = B I IB=BI )
= I + i = 1 n C i n I i B n i =\displaystyle I+\sum_{i=1}^n C_i^n I^i B^{n-i}
= I + i = 1 n C i n B =\displaystyle I+\sum_{i=1}^n C_i^n B ( I I is identity, B B is an idempotent element)
= I + ( 2 n 1 ) B =I+(2^n-1)B
= [ 2 n 3 × 2 n 3 0 1 ] =\begin{bmatrix}2^n&3\times 2^n-3\\0&1\end{bmatrix}
b = ( 3 × 2 20 3 ) 2 ( 3 × 2 19 3 ) + 3 = 6 b=(3\times 2^{20}-3)-2(3\times 2^{19}-3)+3=6



Let A = [ 2 3 0 1 ] = [ 1 0 0 1 ] + [ 1 3 0 0 ] = I + B A=\begin{bmatrix} 2 & 3 \\ 0 & 1 \end{bmatrix} = \begin{bmatrix} 1 & 0 \\ 0 & 1 \end{bmatrix} + \begin{bmatrix} 1 & 3 \\ 0 & 0 \end{bmatrix} = I + B , where B = [ 1 3 0 0 ] B = \begin{bmatrix} 1 & 3 \\ 0 & 0 \end{bmatrix} . We note that B 2 = [ 1 3 0 0 ] [ 1 3 0 0 ] = [ 1 3 0 0 ] = B B^2 = \begin{bmatrix} 1 & 3 \\ 0 & 0 \end{bmatrix}\begin{bmatrix} 1 & 3 \\ 0 & 0 \end{bmatrix} = \begin{bmatrix} 1 & 3 \\ 0 & 0 \end{bmatrix} = B B n = B \implies B^n = B , where n N n \in \mathbb N . Therefore,

A n = ( I + B ) n = I + ( n 1 ) B + ( n 2 ) B 2 + ( n 3 ) B 3 + + ( n n ) B n = I + k = 1 n ( n k ) B k Note that B k = B = I + k = 0 n ( n k ) B B By binomial theorem = I + 2 n B B = I + ( 2 n 1 ) B \begin{aligned} A^n & = (I+B)^n \\ & = I + \binom n1 B + \binom n2 B^2 + \binom n3 B^3 + \cdots + \binom nn B^n \\ & = I + \sum_{k=1}^n \binom nk \color{#3D99F6} B^k & \small \color{#3D99F6} \text{Note that }B^k = B \\ & = I + {\color{#D61F06}\sum_{k=0}^n \binom nk}\color{#3D99F6}B - B &\small \color{#D61F06} \text{By binomial theorem} \\ & = I + {\color{#D61F06}2^n}B - B \\ & = I + (2^n-1)B \end{aligned}

Then we have:

X = A 20 2 A 19 + A = I + ( 2 20 1 ) B 2 ( I + ( 2 19 1 ) B ) + I + B = 2 20 B B 2 20 B + 2 B + B = 2 B = [ 2 6 0 0 ] \begin{aligned} X & = A^{20} - 2A^{19} + A \\ & = I + (2^{20}-1)B - 2\left(I + (2^{19}-1)B\right) + I + B \\ & = 2^{20}B - B - 2^{20}B + 2B + B \\ & = 2B \\ & = \begin{bmatrix} 2 & 6 \\ 0 & 0 \end{bmatrix} \end{aligned}

Therefore, b = 6 b = \boxed{6} .

Shaurya Singh
Apr 29, 2018

We can establish a recurrence A ( n + 1 ) = [ 2 T 11 ( n ) 2 T 12 ( n ) + 3 0 1 ] A(n + 1) = \begin{bmatrix} 2T_{11}(n) & 2T_{12}(n) + 3 \\ 0 & 1 \end{bmatrix} \\

Where A ( 1 ) = [ 2 3 0 1 ] A(1) = \begin{bmatrix} 2 & 3 \\ 0 & 1 \end{bmatrix} , A ( 2 ) = [ 4 9 0 1 ] A(2) = \begin{bmatrix} 4 & 9 \\ 0 & 1 \end{bmatrix} , A ( 3 ) = [ 8 21 0 1 ] , A ( 4 ) = [ 16 45 0 1 ] , A(3) = \begin{bmatrix} 8 & 21 \\ 0 & 1 \end{bmatrix}, A(4) = \begin{bmatrix} 16 & 45 \\ 0 & 1 \end{bmatrix}, \cdots \\

Thus, you can view the above equation as,

A 20 2 A 19 + A = [ T 11 ( n + 1 ) 2 T 11 ( n ) + 2 2 T 12 ( n + 1 ) 2 T 12 ( n ) + 3 0 1 2 + 1 ] = [ 2 b 0 0 ] A^{20} - 2A^{19} + A = \begin{bmatrix} T_{11}(n + 1) - 2T_{11}(n) + 2 & 2T_{12}(n + 1) - 2T_{12}(n) + 3 \\ 0 & 1 -2 +1 \end{bmatrix} = \begin{bmatrix} 2 & b \\ 0 & 0 \end{bmatrix} \\

We can see that A 21 a n d A 22 A_{21} and A_{22} are pretty obvious.

A 11 = T 11 ( n + 1 ) 2 T 11 ( n ) + 2 = 2 T 11 ( n ) 2 T 11 ( n ) + 2 = 2 A_{11} = T_{11}(n + 1) - 2T_{11}(n) + 2 = 2T_{11}(n) - 2T_{11}(n) + 2 = 2 and,

A 12 = T 12 ( n + 1 ) 2 T 12 ( n ) + 3 = 2 T 12 ( n ) + 3 2 T 12 ( n ) + 3 = 6 A_{12} = T_{12}(n+1) - 2T_{12}(n) + 3 = 2T_{12}(n) + 3 - 2T_{12}(n) + 3 = 6 \\

Thus, b = 6 b = 6 .

Richard Xu
Apr 1, 2018

It's actually not necessary to calculate A 19 A^{19} . Instead, assume that

A 19 = [ p q r s ] A^{19} = \begin{bmatrix} p & q \\ r & s\end{bmatrix}

Then we can write out

[ 0 3 0 1 ] [ p q r s ] = [ 0 b 3 0 1 ] \begin{bmatrix}0 & 3 \\ 0 & -1\end{bmatrix} \begin{bmatrix}p & q \\ r & s\end{bmatrix}= \begin{bmatrix}0 & b-3 \\ 0 & -1\end{bmatrix}

Therefore

{ 3 s = b 3 s = 1 b = 6 \left\{\begin{aligned}3s &= b-3\\ -s &= -1 \end{aligned}\right. \Rightarrow b= 6

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...